Erratum: Johnson et al. Alston Virus, a Novel Paramyxovirus Isolated from Bats Causes Upper Respiratory Tract Infection in Experimentally Challenged Ferrets. Viruses 2018, 10, 675 - Rebecca I. Johnson; Mary Tachedjian; Brenton Rowe; Bronwyn A. Clayton; Rachel Layton; Jemma Bergfeld; Lin-Fa Wang; Ina L. Smith; Glenn A. Marsh (Viruses, 2021)
The authors wish to make the following erratum to this paper [...]